NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM ANIME ONE PIECE ARC ALABASTA - Lira, Rahmat Adnan (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
This study aims to describe the values of Islamic education contained in the anime One Piece Arc Alabasta using a qualitative approach. The type of research used in this research is library research which makes the anime film One Piece Arc Alabasta the object of study. The primary data source in this study is the anime One Piece Arc Alabasta, while the secondary data sources are books, articles and journals related to research. Data collection is carried out by watching the anime One Piece Arc Alabasta and then recording the parts (scenes and dialogues) related to the research. Furthermore, the research data obtained are then analyzed using the method of reduction, presentation and conclusion. The results that is found in this study indicate that there are two values of Islamic education in the anime one piece arc Alabasta, namely 1) I'tiqodiyah values a) gratitude, b) Sincerity and patience, 2) Khuluqiyyah values a) Mutual help, b) Mutual trust/kind suspicion, c) Affection.